Pemanfaatan Pemodelan 3d Sketchup Dalam Analisis Risiko Ergonomi Dan Perancangan Stasiun Kerja Yang Berkelanjutan - Venus Khatta Salsabillah; Anang Siswanto (Ekliptika, 2026)
This qualitative study evaluates the effectiveness of SketchUp as a visualization tool for ergonomic workstation design. Findings indicate that 3D visualization accelerates the identification of work positions that pose a risk to worker health. Using SketchUp allows for the simulation of facility layouts that support occupational safety and operational comfort, in accordance with sustainable industrial principles. The analysis was conducted by converting the research subjects' experiences in digital modeling into technical data on musculoskeletal risks. The study concludes that the integration of 3D technology and national ergonomic standards is a crucial pillar in achieving energy efficiency and social well-being in industrial environments.